Komunikasi Pemasaran Kebun Binatang Surabaya Melalui Media Sosial TikTok @Kebunbinatangsurabaya - Delang, Marselinus Putra Raga; Ratna Puspita Sari; Salahudin Al Afgan (LPPM Stikosa-AWS, 2024)
Nowadays, social media accounts can be utilized in various ways. One way is by promoting tourist areas. One of the tourist areas in the city of Surabaya, namely the Surabaya Zoo, has utilized social media as a tourism promotion medium such as Facebook, Twitter, YouTube and also TikTok. This research focuses on the social media TikTok which is now widely used by business people to promote their products. This research reviews how the use of TikTok features related to forms of promotion is in accordance with the promotion mix including advertising, sales promotion, public relations and personal selling using qualitative descriptive research methods on the TikTok @kebunbinatangsurabaya account. In the process of using TikTok as an online promotional media for TikTok @kebunbinatangsurabaya has fulfilled the criteria contained in the four promotional mixes so that the use of TikTok based on the Followers, Feed, Like, Coment, Hashtag features has supported a good promotional process.